1998
DOI: 10.1007/s001090050227
|View full text |Cite
|
Sign up to set email alerts
|

Expression of type III hyperlipoproteinemia in patients homozygous for apolipoprotein E-2 is modulated by lipoprotein lipase and postprandial hyperinsulinemia

Abstract: Type III hyperlipoproteinemia (HLP) is a multifactorial disorder associated with homozygosity for the apolipoprotein (apo) E-2 allele. Factors which may promote the development of HLP include lipoprotein lipase (LPL) and hyperinsulinemia. These factors were investigated in eight patients with type III HLP and in nine normolipidemic controls. In vitro the interaction of apoE with LPL was analyzed in cell binding assays. All type III HLP patients showed delayed triglyceride (TG) clearance and remnant lipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…This is in line with our previous findings in a smaller group of apoE2 homozygotes. 20 Recently, Brümmer et al 23 have compared 8 type III HLP patients and 3 normolipidemic E2/2 subjects. Their study demonstrated increased postprandial insulin levels but normal fasting insulin levels in type III HLP patients, which were most likely due to the small sample size.…”
Section: Scatterplots Showing the Associations Between Total Triglycementioning
confidence: 99%
“…This is in line with our previous findings in a smaller group of apoE2 homozygotes. 20 Recently, Brümmer et al 23 have compared 8 type III HLP patients and 3 normolipidemic E2/2 subjects. Their study demonstrated increased postprandial insulin levels but normal fasting insulin levels in type III HLP patients, which were most likely due to the small sample size.…”
Section: Scatterplots Showing the Associations Between Total Triglycementioning
confidence: 99%
“…Based on 13 studies published up to 1997 (27), Asn291Ser heterozygous carriers had an average increase in plasma TG of 31% and an average decrease in HDL-C of 0.12 mM (P , 0.001). However, since then, a number of other studies have been published in which no association was observed (10,18,20,21,24). In addition to study power and other methodological issues, interactions with important dyslipidemic risk factors such as increasing age and weight gain could have resulted in heterogeneous findings.…”
mentioning
confidence: 99%
“…The secondary types include: (1) an "acquired secondary" subtype, which is seen in patients who are hypothyroid, have poorly-controlled diabetes mellitus, are uremic, have dysglobulinemia, or are treated with ␤-blockers and/or thiazides [19][20][21], and (2) a familial secondary subtype that is seen in conjunction with other primary hyperlipidemias, such as familial combined hyperlipidemia and hepatic lipase deficiency [8,20]. The primary types of dysbetalipoproteinemias are of familial nature, and include patients that are: (1) homozygous for the ⑀2 locus of apo-E (⑀2/⑀2 genotype) [5,8,9]; (2) homozygous for other, less common apo-E variants that have low affinity to the hepatic apo-B/apo-E (LDL) receptors [4,[22][23][24]; and (3) patients with apo-E deficiency [25].…”
Section: Discussionmentioning
confidence: 99%
“…Apo-E plays an important role in lipoprotein metabolism caused by its location on apo-Bcontaining particles, but is also found on some high-density lipoprotein (HDL) particles. The development of FDB is frequently secondary to other concomitant genetic or environmental factors, which lead to the emergence of the overt phenotype of this particular dyslipidemia [3,9]. With regard to HDL levels in patients with FDB, these are usually only mildly decreased, and often correlate inversely with serum TG levels [10].…”
mentioning
confidence: 97%
See 1 more Smart Citation